The Incidence of Iliopsoas Tendinopathy and Labral Tears on High Resolution MRI, An Observational Study - Saad, Ahmed; Chan, Roger; Iqbal, Aamer; Davies, Mark; James, Steven; Botchu, Rajesh (Acta medica Lituanica, 2023)
Introduction. Labral tears (LT) can present with hip or groin pain. Investigation of LT is typically with Magnetic Resonance Arthrography (MRA). The injection of contrast for MRA can lead to fluid signal intensity/oedema on fluid sensitive sequences within the iliopsoas muscle and tendon complex masking the diagnosis of iliopsoas tendinopathy, which may present with similar symptoms. The aim of this study was to identify the presence of iliopsoas oedema in young adult patients being investigated for LT. Material and methods. We performed a retrospective search of our radiology system for the word ‘labral tear’ in the reports of patients who had MRI between 2012 to 2018. Patients under the age of 40 years who underwent high resolution dedicated hip MRI were included in our study. From this database, we then used a keyword search ‘strain and (o)edema’ to identify cases of iliopsoas pathology and analysed the results. Results. We identified 1151 consecutive cases of high resolution hip MRI with a suspected labral tear. 503 patients under the age of 40 years were included in our study with the average age of 27 years. Of the 503 patients within our cohort, searching for the word ‘strain’ identified 48 (9.5%) cases. Of these, 26 (5.3%) patients had iliopsoas oedema with a labral tear. 22 (4.4%) patients had iliopsoas oedema without a labral tear. Conclusion. Our study shows that 4.4% of patients undergoing MRA have no labral tears but iliopsoas oedema. Patients should undergo MRI to exclude iliopsoas strains before MRA.